2017
DOI: 10.1073/pnas.1618293114
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated fatty acyl recognition by Frizzled receptors mediates dimerization upon Wnt ligand binding

Abstract: Frizzled (FZD) receptors mediate Wnt signaling in diverse processes ranging from bone growth to stem cell activity. Moreover, high FZD receptor expression at the cell surface contributes to overactive Wnt signaling in subsets of pancreatic, ovarian, gastric, and colorectal tumors. Despite the progress in biochemical understanding of Wnt-FZD receptor interactions, the molecular basis for recognition of Wnt cis-unsaturated fatty acyl groups by the cysteine-rich domain (CRD) of FZD receptors remains elusive. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 44 publications
12
111
0
Order By: Relevance
“…It is clear that the hydrophobic channel on the FZD CRD has a strong preference for binding fatty acids or other lipid-like molecules. Indeed, a recent crystal structure of the hFZD7 CRD showed the hydrophobic channel occupied by a fatty acid that originated in the cells used for protein expression – which do not overexpress a Wnt (Nile et al, 2017). In this study and another (DeBruine et al, 2017), it was further shown that binding of free fatty acids induces FZD-CRD oligomerization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that the hydrophobic channel on the FZD CRD has a strong preference for binding fatty acids or other lipid-like molecules. Indeed, a recent crystal structure of the hFZD7 CRD showed the hydrophobic channel occupied by a fatty acid that originated in the cells used for protein expression – which do not overexpress a Wnt (Nile et al, 2017). In this study and another (DeBruine et al, 2017), it was further shown that binding of free fatty acids induces FZD-CRD oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…This structure confirmed that a conserved serine (S187 in xWnt8) is the only acylation site, and suggested that the S187-linked palmitoleoyl moiety plays a crucial role in FZD binding by occupying a hydrophobic channel on the CRD. This hydrophobic channel also binds free fatty acids in a manner thought to promote FZD oligomerization (DeBruine et al, 2017; Nile et al, 2017). Since all Wnts except WntD are predicted to be acylated at this conserved serine (Nile and Hannoush, 2016; Takada et al, 2006), it is thought that Wnts all engage and activate FZDs through such acylation-dependent interactions (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the linker cysteines for receptor function is further underlined by previous reports identifying FZD 4 familial exudative vitreoretinopathy (FEVR) mutations in Cys-181 and Cys-204 of human FZD 4 (57)(58)(59). These C181R, C204R, C204Y mutations (corresponding to Cys-161 and Cys-185 in human FZD 6 , respectively) manifested with a trafficking phenotype and poor receptor surface expression (57,58).…”
Section: The Linker Domain Of Frizzledmentioning
confidence: 91%
“…FZDs, the focus of this study, bind WNT proteins with their extracellular cysteine-rich domain (CRD) to initiate a complex network of WNT signaling pathways (2). The CRD is seen as the orthosteric binding site for WNTs and is functionally implicated in receptor dimerization and signal initiation (3)(4)(5)(6). Structurally, the CRD is connected to the seven transmembrane (7TM) core of the receptor through a linker domain of variable length and low degree of conservation among the representatives of class F (5).…”
mentioning
confidence: 99%
“…Furthermore, recent observations from the crystal structure of the Fzd7 CRD bound to a fatty acid has revealed that the palmitoleic lipid adduct binds to a U-shaped lipidbinding cavity of the Fzd7 dimer. Fzd5 and Fzd8 have similar architectures, including a dimeric arrangement of the CRD, suggesting a common model for how Wnt binds Fzd receptors via the fatty acid modification (Nile et al, 2017).…”
Section: Introductionmentioning
confidence: 99%